Occupational Dermatoses by Type of Work in Greece - Eleni Zorba; Antony Karpouzis; Alexandros Zorbas; Theodore Bazas; Sam Zorbas; Elias Alexopoulos; Ilias Zorbas; Konstantinos Kouskoukis; Theodoros Konstandinidis (Elsevier, 2013)
Background: To elucidate the relationship between seven occupational dermatoses (ODs) and 20 types of work in Greece. Methods: This was a prevalence epidemiologic study of certain ODs among 4,000 workers employed in 20 types of enterprise, in 104 companies, in 2006-2012, using data from company medical records, questionnaires, occupational medical, and special examinations. The χ2 test was applied to reveal statistically significant relationships between types of enterprises and occurrence of ODs. Results: A high percentage (39.9%) of employees included in the study population suffered from ODs. The highest prevalence rates were noted among hairdressers (of contact dermatitis: 30%), cooks (of contact dermatitis: 29.5%), bitumen workers (of acne: 23.5%), car industry workers (of mechanical injury: 15%), construction workers (of contact urticaria: 29.5%), industrial cleaning workers (of chemical burns: 13%), and farmers (of malignant tumors: 5.5%). We observed several statistical significant correlations between ODs (acute and chronic contact dermatitis, urticaria, mechanical injury, acne, burns, skin cancer) and certain types of enterprises. There was no statistically significant correlation between gender and prevalence of ODs, except for dermatoses caused by mechanical injuries afflicting mainly men [χ2 (1) = 13.40, p < 0.001] and for chronic contact dermatitis [χ2 (1) = 5.53, p = 0.019] afflicting mainly women. Conclusion: Prevalence of ODs is high in Greece, contrary to all official reports by the Greek National Institute of Health. There is a need to introduce a nationwide voluntary surveillance system for reporting ODs and to enhance skin protection measures at work.